PENGARUH SUHU PADA PROSES PENGENDAPAN SANTAN KELAPA DALAM PEMBUATAN VIRGIN COCONUT OIL (VCO) - Agustrian; Rahmawati, Rahmawati (Jurnal Penelitian Fisika dan Terapannya (JUPITER), 2023)
Indonesia is one of the large and wide countries that has a tropical climate because it is located on the equator. So that there is a lot of diversity of plants that live in tropical areas, namely coconut plants. The coconut fruit can be used as a variety of processed products, one of which is coconut oil. This study aims to analyze the effect of temperature on the deposition of coconut milk in the manufacture of Virgin Coconut Oil (VCO) to determine the value of density, viscosity, aroma, color, and flavor. This research was conducted at the Biology Laboratory of the University of PGRI Palembang in June 2022. The method used in this research is the experimental method. Data collection was carried out in the Biology Laboratory and then data testing was carried out in the Lab. Sriwijaya State Polytechnic Chemical Engineering. The results showed that for the coconut oil sample at a temperature of 800C the density value was 0.918 or 0.92 gr/cm3 according to the SNI standard density in the range of 0.91-0.92 gr/ml, viscosity value 57.26 mPa.s, oil color clear coconut, the characteristic aroma of coconut oil, and the tasteless taste. As for the temperature of 1000C, the density value is 0.92 gr/cm3 based on the SNI standard (Firdausi et al., 2008), the viscosity value is 63.83 mPa.s, the color of the coconut oil is clear, the distinctive aroma of coconut oil, the tasteless taste is according to the SNI 7381 standard:2005 (Alamsyah, 2005). From the results of the study it is said that temperature affects the process of making coconut oil.